Gain of function in somatic TP53 mutations is associated with immune‐rich breast tumors and changes in tumor‐associated macrophages. Issue 12 (22nd October 2019) - Behring, Michael; Vazquez, Ana I.; Cui, Xiangqin; Irvin, Marguerite R.; Ojesina, Akinyemi I.; Agarwal, Sumit; Manne, Upender; Shrestha, Sadeep
Abstract: Background: Somatic mutations in TP53 are present in 20%–30% of all breast tumors. While there are numerous population‐based analyses of TP53, yet none have examined the relationship between somatic mutations in TP53 and tumor invasive immune cells. Methods: Clinical and genetic data from 601 women drawn from The Cancer Genome Atlas (TCGA) were used to test the association between somatic TP53 mutation and immune‐rich or immune‐poor tumor status; determined using the CIBERSORT‐based gene expression signature of 22 immune cell types. Our validation dataset, the Molecular Taxonomy of Breast Cancer International Consortium (METABRIC), used a pathologist‐determined measure of lymphocyte infiltration. Results: Within TP53 ‐mutated samples, a mutation at codon p.R175H was shown to be present at higher frequency in immune‐rich tumors. In validation analysis, any somatic mutation in TP53 was associated with immune‐rich status, and the mutation at p.R175H had a significant association with tumor‐invasive lymphocytes. TCGA‐only analysis of invasive immune cell type identified an increase in M0 macrophages associated with p.R175H. Conclusions: These findings suggest that TP53 somatic mutations, particularly at codon p.R175H, are enriched in tumors with infiltrating immune cells. Our results confirm recent research showing inflammation‐related gain of function in specific TP53 mutations. Abstract : The occurrence of somatic mutations in TP53 was found to be higher in immune‐rich breast tumors. We found that a single somatic variant of TP53, p.R175H, occurs at a higher frequency in immune‐rich breast tumors. This mutation was also associated with a decreased proportion of tumor‐invasive M1 macrophages, and increased M0 macrophages.